2001
DOI: 10.1152/jn.2001.86.3.1481
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms That Initiate Spontaneous Network Activity in the Developing Chick Spinal Cord

Abstract: Many developing networks exhibit a transient period of spontaneous activity that is believed to be important developmentally. Here we investigate the initiation of spontaneous episodes of rhythmic activity in the embryonic chick spinal cord. These episodes recur regularly and are separated by quiescent intervals of many minutes. We examined the role of motoneurons and their intraspinal synaptic targets (R-interneurons) in the initiation of these episodes. During the latter part of the inter-episode interval, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(104 citation statements)
references
References 48 publications
(47 reference statements)
8
96
0
Order By: Relevance
“…White Leghorn chicken embryos (Hy-Line Hatcheries) were dissected as described in ref. 48. Briefly, spinal cords from stage 36 (E10) embryos were isolated with intact muscle nerves.…”
Section: Methodsmentioning
confidence: 99%
“…White Leghorn chicken embryos (Hy-Line Hatcheries) were dissected as described in ref. 48. Briefly, spinal cords from stage 36 (E10) embryos were isolated with intact muscle nerves.…”
Section: Methodsmentioning
confidence: 99%
“…Our next goal was to show that these light-sensitive proteins could be used to control circuit behavior in whole animal preparations. Early embryonic chick spinal cords exhibit rhythmic episodes of spontaneous bursting activity, which are generated by recurrent excitatory connections between motoneurons and GABAergic and glycinergic interneurons, all of which are excitatory at this stage of development (23)(24)(25). Recently, it has been shown that the normal pattern and frequency of this early spontaneous activity is required for appropriate motor axon pathfinding in the chick (14) and for the development of cord circuits that enable appropriate flexorextensor and right-left phasing during locomotor-like activity in the mouse (26).…”
Section: Activation Of Ro4 and Chr2 Can Be Used To Control Spontaneousmentioning
confidence: 99%
“…This finding was not entirely unexpected because regions of cord not electroporated with RO4 would still be able to depolarize and contribute to the excitation required to elicit a bursting episode (see ref. 23) for details of episode generation). Surprisingly, however, a 2-s pulse of light actually elicited a premature episode (4I, 2) 1 min after a spontaneous episode (Fig.…”
Section: Activation Of Ro4 and Chr2 Can Be Used To Control Spontaneousmentioning
confidence: 99%
“…13,19 Studies of the developing chick cord showed that spinal networks experience transient increases in synaptic activity, presumably arising from the coordinated firing of clusters of neurons, and that these events can trigger synchronized network activity. 19 The ensemble activity of these networks allows the chick to synchronize motor activity (co-contractions) to break out of the shell, and then changes in organization allow the chick to manifest bipedal (alternating) locomotion while maintaining the ability to co-contract. 17 Gap junctions are required for synchronizing the oscillatory responses of neurons and for clustering of coherent rhythmic activity.…”
Section: Onset Of Hyperreflexia In Sci C Yates Et Almentioning
confidence: 99%